Evaluation of the “50-50 criteria” of post-hepatectomy liver failure as mortality predictor after resection of liver tumors - El-Badry, Ashraf M.; Ahmed, Ahmed E. (International Surgery Journal, 2019)
Background: Post-hepatectomy liver failure (PHLF) represents a serious complication of liver resection. A standardized definition of PHLF based on serum total bilirubin (TB) level and prothrombin time (PT) reduction at the fifth postoperative day (POD-5) gained wide popularity. Methods: Medical records of consecutive adult patients who underwent elective liver resection for hepatic neoplasms from May 2015 to April 2018 were prospectively collected. PHLF was defined as serum total bilirubin (TB) level >50 mmol and prothrombin time (PT) reduction <50% on the fifth postoperative day (POD-5). Patients with PHLF were identified as group A and compared with group B (without PHLF) regarding postoperative complications and mortality. Results: Fifty-one patients were enrolled, forty-three with malignant (primary and secondary) neoplasms and eight with benign liver masses. Group A comprised eight patients who fulfilled the criteria of PHLF whereas 43 patients were included in group B. The mean age, gender ratio and mean number of resected liver segments were not significantly different between both groups. Patients in group A exhibited significantly increased complication rates compared with group B. Postoperative mortality occurred exclusively in group A where five among eight patients (62.5%) died postoperatively. The mortality rate was remarkably higher (100%) in cirrhotic patients who developed PHLF compared with 40% in non-cirrhotic with PHLF. Conclusions: PHLF is associated with increased severity of postoperative complications and mortality. Development of PHLF prompts intensive treatment protocol, particularly in cirrhotic patients.